2017
DOI: 10.1007/s12149-017-1202-3
|View full text |Cite
|
Sign up to set email alerts
|

Bone metastases from breast cancer: associations between morphologic CT patterns and glycolytic activity on PET and bone scintigraphy as well as explorative search for influential factors

Abstract: BackgroundThis study aimed to compare the detection of bone metastases from breast cancer on F-18 fluorodeoxyglucose positron emission tomography (FDG-PET) and bone scintigraphy (BS). An explorative search for factors influencing the sensitivity or uptake of BS and FDG-PET was also performed.MethodsEighty-eight patients with bone metastases from breast cancer were eligible for this study. Histological confirmation of bone metastases was obtained in 31 patients. The bone metastases were visually classified into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
60
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(66 citation statements)
references
References 17 publications
3
60
1
Order By: Relevance
“…In a retrospective Japanese study of 88 breast cancer patients with bone metastasis, they found higher lesion-based sensitivity (94%) for FDG-PET/CT than for CT and BS (77% and 89%, respectively), which were in line with the results of our study. However, they found a relatively lower detection of osteosclerotic lesions for FDG-PET/CT than other lesion types [ 13 ], which was not confirmed by our study. Additional to the results of previous studies regarding the superiority of FDG-PET/CT in detection of bone metastases compared to BS [ 11 , 12 , 15 ], our study showed that LDCT and BS combined could provide sensitivity equal to that of FDG-PET/CT in detection of skeletal metastases.…”
Section: Discussioncontrasting
confidence: 95%
“…In a retrospective Japanese study of 88 breast cancer patients with bone metastasis, they found higher lesion-based sensitivity (94%) for FDG-PET/CT than for CT and BS (77% and 89%, respectively), which were in line with the results of our study. However, they found a relatively lower detection of osteosclerotic lesions for FDG-PET/CT than other lesion types [ 13 ], which was not confirmed by our study. Additional to the results of previous studies regarding the superiority of FDG-PET/CT in detection of bone metastases compared to BS [ 11 , 12 , 15 ], our study showed that LDCT and BS combined could provide sensitivity equal to that of FDG-PET/CT in detection of skeletal metastases.…”
Section: Discussioncontrasting
confidence: 95%
“…Our study revealed weak sensitivity for PET just 16.7% while CT showed 100% sensitivity. A study made by Sugihara et al [10] found the sensitivity of PET was 69% (11/16). This difference can be explained by the smaller sample size in our study for the osteoblastic metastases.…”
Section: Discussionmentioning
confidence: 97%
“…In bony lytic lesions, it is reported that CT has lower sensitivity than PET. A study conducted by Sugihara et al [10] revealed sensitivities of CT and PET were 77.9% and 94% respectively. Our study revealed similar sensitivities where it was for CT 89% and for PET it was 100%.…”
Section: Discussionmentioning
confidence: 97%
“…Aquiduo PET/CT scanner has the following technical characteristics: detector material, Lu 2 SiO 5 (Ce) (LSO); crystal size, 4.0 × 4.0 × 20 mm 3 ; detector ring diameter, 830 mm; transaxial field of view (FOV), 585 mm; axial FOV, 162 mm, coincidence window, 4.5 ns; energy window, 425–650 keV; maximum ring difference, 27; random correction, delayed; scatter correction, single scatter simulation. Emission data were acquired for 2–3 min per bed position 17 . The PET images were reconstructed using an iterative algorithm (the combination of Fourier rebinning and the ordered subsets expectation–maximization [FORE + 2D-OSEM]; 4 iterations, 14 subsets) with an 8-mm Gaussian filter, a 128 × 128 matrix (3.9 mm/pixel) and 81 slices (2 mm/slice).…”
Section: Methodsmentioning
confidence: 99%